Recent Advances in the Synthesis, Functionalization and Applications of Pyrazole-Type Compounds I - Silva, Vera L. M.; Silva, Artur M. S. (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Pyrazoles and their reduced form, pyrazolines, are considered privileged scaffolds in medicinal chemistry, owing to their noteworthy biological activities, physicochemical properties and occurrence in many low-molecular-weight compounds present in several marketed drugs (e.g., Celebrex® and Viagra®). Pyrazoles are also found in a variety of agrochemicals (fungicides, insecticides, and herbicides) and are versatile compounds for synthetic manipulations. Their challenging chemical structures and properties (mainly tautomerism, with possible implications in their reactivity), and diverse applications, have attracted the attention of many researchers who have developed various synthetic approaches. This reprint presents some examples of the most recent advances in pyrazoles' chemistry, including synthetic methodologies to access novel pyrazole derivatives, to their functionalization, and studies of their properties and applications in different fields, mainly in medicine and materials science.